Pandangan Hukum Islam terhadap Fenomena Penggunaan Kata “Anjay” dalam Pergaulan Remaja - Fuadi Isnawan (IAI Darussalam, 2021)
This study focuses on the association of today's teenagers with increasingly complex and diverse relationships in their daily interactions. This complex interaction spawned a new culture in communication, namely using swear words in responding to certain things. One of the popular words is the word